2017
DOI: 10.15414/jmbfs.2017.7.1.62-66
|View full text |Cite
|
Sign up to set email alerts
|

EXPLORING THE MILK-CLOTTING PROPERTIES OF EXTRACTS FROM Bromelia pinguin FRUIT

Abstract: Plants represent an attractive source of milk-clotting proteases with potential use for chymosin substitution in cheesemaking process. A crude enzymatic extract from B. pinguin fruit showed capacity to clot milk efficiently in a short time. It showed a maximum milk-clotting activity around 4 U/mL in the range of 70-80 ºC. This value indicated that one mL of the extract was capable to clot around 400 mL of milk in 40 min at the specified condition. B. pinguin extract presented only 25% of its maximum activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Similar results were obtained by Moreno-Hernández et al (44) who found that crude extract from Bromelia pinguin L. fruit showed an efficient capacity to clot milk in a short time with a maximum MCA of around 3.99 U/ml.…”
Section: Milk Coagulation Study (Mca Sa and Pa)supporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were obtained by Moreno-Hernández et al (44) who found that crude extract from Bromelia pinguin L. fruit showed an efficient capacity to clot milk in a short time with a maximum MCA of around 3.99 U/ml.…”
Section: Milk Coagulation Study (Mca Sa and Pa)supporting
confidence: 89%
“…In the cheese industry, the coagulation enzymes used are always sought to have a high coagulant activity and a low proteolytic activity (48), so CCE seemed to be the best because excessive proteolysis can lead to a decrease in cheese yield due to loss of peptides in the whey and defects in taste such as bitterness and texture of the ripened cheese (49). The PA values in this study were lower than those of other studies such as that of Withania coagulans fruit extract (30) and Bromelia pinguin fruit extract (44) with 1.06 U/mg-and 2.0 U/mg respectively. The MCA/PA ratio is one of the most important properties of the enzymes used in cheese making, which is the index of coagulation efficiency and suitability of the extract to be used as a substitute for rennet (50).…”
Section: Milk Coagulation Study (Mca Sa and Pa)mentioning
confidence: 69%
See 1 more Smart Citation